Epistemologi Pendidikan Islam Perspektif Abed Al Jabiri - A Faisol Haq (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
The discussion of epistemology up to date is still very interesting to be examined, because in a epistemology is a way of gaining a knowledge,scientific study will never go off the way and method to get to A knowledge it self, as well as Islamic education also requires the study of epistemology in education. In this paper try to open the epistemology of Abed Al-Jabiri with the reason bayani, reason Burhani and Onebill reason which was then used as a foundation in Islamic education epistemology.